KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN IPS PADA KURIKULUM MERDEKA DI MI AL FITHRAH SURABAYA - Dewi Ixfina, Ficky (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the readiness of teachers in the planning, implementation, and evaluation of Social Studies (IPS) learning in Grade 3 at MI Al Fithrah Surabaya. The research employed a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings reveal that teachers have made efforts to implement the principles of the Merdeka Curriculum in Social Studies instruction, including student-centered approaches and explorative, participatory, and contextual learning activities. The evaluation process is conducted comprehensively, covering cognitive, affective, and psychomotor domains, and includes feedback to parents. Nevertheless, teachers still face several challenges, such as difficulties in analyzing student characteristics, limited use of instructional media, and insufficient variation in teaching methods. Teachers' professional development efforts through teacher working groups (KKG) and training programs reflect their commitment to improving learning quality. Continuous support from both the school and the government in the form of training and technical assistance is essential.